UPAYA PENINGKATAN KUALITAS PELAYANAN PEGAWAI UNIT PELAYANAN TEKNIS DAERAH (UPTD) - Sugiantiningsih Agung; Cok Istri Mas Kusumaningrat; I Ketut Gede Gandhi Coryka (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2020)
Improving professionalism means improving the quality of service to the public. This urgent matter has to be done with good planning and directing so that the good service could be sustainable. However, in the one-roof public service unit sub-branch Kuta office or Unit Pelayanan Teknis Daerah (UPTD), this matter lacked attention. Consequently, the performance of the civil servants in this unit had not improved. This study was held based on the consideration that the bureaucracy in this unit was too complicated that it could lead to bribery and extortion. The author used quantitative approach and collected the data by giving questionnaire and documenting (that resulted in qualitative data). Based on the analysis, the author concluded that the efforts to improve the service quality to the public in this could be done well. Peningkatan kualitas pelayanan pegawai menjadi sangat urgen dan perlu dilakukan secara terencana, terarah, dan berkesinambungan dalam rangka meningkatkan kemampuan dan profesionalisme. Namun disisi lain yang terjadi pada Unit Pelayanan Teknis Daerah (UPTD) cabang pembantu Kantor Samsat Kuta, Peningkatan kualitas pegawai sering kurang mendapat perhatian. Adanya kendala mengenai pengembangan kemampuan pegawai menyebabkan kualitas kerja cenderung belum dapat diwujudkan. Atas latar pemikiran diatas penulis mengangkat judul